Endocircular Li carbon rings - Yang, Yi-Fan; Cederbaum, Lorenz S. (Angewandte Chemie. International edition, 2021)
By employing accurate state-of-the-art many-electron quantum-chemistry methods, we establish that monocyclic carbon rings can accommodate Li guest atoms. The low-lying electronic states of these endocircular systems are analyzed and found to include both charge-separated states where the guest Li atom appears as a cation and the ring as an anion and encircled-electron states where Li and the ring are neutral. The electron binding energies of the encircled-electron states increase drastically at their highly symmetric equilibrium geometries with increasing size of the ring, and in LiC24, this state becomes the ground state. Li is very weakly bound vertical to the rings in the low-lying encircled-electron states, hinting to van-der-Waals binding. Applcations are mentioned.